Tumor dormancy and relapse: from a natural by-product of evolution to a disease state - Manjili, Masoud H. (Cancer Res, 2017)
Species evolve by mutations and epigenetic changes acting on individuals in a population; tumors evolve by similar mechanisms at a cellular level in a tissue. This paper reviews emerging evidence about tumor dormancy and suggests that: i) cellular malignancy is a natural by-product of evolutionary mechanisms such as gene mutations and epigenetic modifications, which is manifested in the form of tumor dormancy in healthy individuals as well as in cancer survivors, ii) cancer metastasis could be an early dissemination event that could occur during malignant dormancy even before primary cancer is clinically detectable, and iii) chronic inflammation is a key factor in awakening dormant malignant cells at the primary site, leading to primary cancer development, and at distant sites, leading to advanced stage diseases. Based on these evidence, it is reasonable to propose that we are all cancer survivors rather than cancer free individuals because of harboring dormant malignant cells in our organs. A better understanding of local and metastatic tumor dormancy could lead to novel cancer therapeutics for the prevention of cancer.